To Promote the Importance of Developing Folk and Traditional Performing Arts in Uzbekistan - Sohibjonovich, Orifjonov Khusniddin; kizi, Rustamjonova Dilhavas Ravshvnbek (Research Parks Publishing LLC, 2023)
It discusses the development of Uzbek oral creativity, folklore and professional genres of Uzbek music. The development process of traditional performance art is analyzed in detail.